A Study on the Difference in Eating Habits of Male University Students by Their Healthy Lifestyle: Focusing on the Male University Students of Military Major (Cuestiones de Fisioterapia, 2024)
Establishing healthy eating habits among university students is crucial, as the period of university life marks the transition from parental control for many students, allowing them to engage in independent eating habits and establish dietary and lifestyle patterns that will persist into adulthood and old age. This study aims to investigate the healthy lifestyles and eating habits of male university students and to understand the impact of healthy lifestyles on eating habits. It intends to identify the patterns of healthy lifestyles and eating habits among the students and to verify the differences in eating habits based on their healthy lifestyles. Based on this, the research questions were formulated, and an investigation was conducted. The results are as follows. It was observed that there were significant differences in eating habits based on the healthy lifestyles of male university students. Specifically, significant differences were observed in terms of daily meal frequency, overeating frequency, processed food consumption frequency, usual dietary issues, eating habits, preference for seasoning, preferred types of food, and water intake among male university students based on their sleep habits, alcohol consumption, alcohol consumption frequency, portion size, and physical exercise. From the results of this study, it can be inferred that there is a correlation between healthy lifestyles and eating habits of male university students. Furthermore, it was found that sleep habits are associated with several eating behaviors. Therefore, it can be deduced that improving exercise and sleep quality would likely be effective in enhancing eating behaviors.